Tughtigin, Ruler of Damascus: Struggle with the Crusaders, War, and Alliance - Birsel Küçüksipahioğlu (Şarkiyat Mecmuası)
During the Crusades, which officially began in 1095, the Turks carried out the fight against the Crusaders with great devotion and zeal. The strategy and success of the Turkish Seljuk Sultan Kilij Arslan I against the Crusaders, who made Anatolia impassable against them Crusaders were important. In 1108, the struggle against the Crusaders was turned into a state policy by the Great Seljuk Empire, and Sultan Muhammad Tapar appointed Mawdūd, amīr of Mosul, to this task. The process that started with Mawdūd and continued with Imād al-Dīn Zangī and Nūr al-Dīn Maḥmūd Zangī was supported by Belek, Aksunkur al-Bursukī, Ilghāzī and Tughtigin, the Atabeg of Damascus. It is known that Tughtigin was a supporter of the Seljuk Malik of Syria Tutush, who impressed the malik with his diligence and success. For, this reason, he was appointed atabeg to his son Dukāk by Tutush. After Dukāk’s death in 1104, he began his political formation and established the Atabegate of Damascus or Tughtiginites. Tughtigin, who treated his people generously and fairly throughout his independent rule, fought against the Crusaders and did not hesitate to ally with them due to the conditions of the period.